1995
DOI: 10.4315/0362-028x-58.5.515
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Problem in Spanish North-Coast Honey

Abstract: Twenty-one samples from the Cantabrian coast were analyzed to establish their microbiological quality and fermentation tendency. In a food with a very low free-water content like honey, microbiological growth is only possible when there is an increase in water activity. Since most of the samples studied were not extensively granulated, the risk of fermentation is mostly due to high water content. Among our samples, only two had a water content below 17.1% (no risk of fermentation), whereas the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 0 publications
0
24
0
3
Order By: Relevance
“…These studies were done at air humidity below 60%, since above that humidity it was found that honey from Apis mellifera absorbed water (Salamanca Grosso et al, 2001). This could be the case of our work done in yatei honey, since time and temperature had a significant effect on the humidity of the honey (Table 1) Sanz et al (1995), and White (1975) described that the fermentation of the honey depends on the initial contamination, the storage time, temperature and the moisture content, this last one being the main factor. The high humidity of the sample ( Figure 2B) associated with the high microbiological load (Table 2) and the effect of the temperature, justifies the development of fermentation and the increase of the acidity in the samples preserved at room temperature (Figure 2A).…”
Section: Humiditymentioning
confidence: 84%
See 1 more Smart Citation
“…These studies were done at air humidity below 60%, since above that humidity it was found that honey from Apis mellifera absorbed water (Salamanca Grosso et al, 2001). This could be the case of our work done in yatei honey, since time and temperature had a significant effect on the humidity of the honey (Table 1) Sanz et al (1995), and White (1975) described that the fermentation of the honey depends on the initial contamination, the storage time, temperature and the moisture content, this last one being the main factor. The high humidity of the sample ( Figure 2B) associated with the high microbiological load (Table 2) and the effect of the temperature, justifies the development of fermentation and the increase of the acidity in the samples preserved at room temperature (Figure 2A).…”
Section: Humiditymentioning
confidence: 84%
“…The production of acids in honey is given not only by the enzymatic action of the glucose oxidase (De Mera & Angert, 2004;Fangio et al, 2007), but also by the fermentative processes developed by the microorganisms present in the matrix (Sanz et al, 1995;White, 1975). The cooling temperature reduces both phenomena, causing decreases of the acidity.…”
Section: Aciditymentioning
confidence: 99%
“…The moisture content of honey types differs significantly and mainly depends on harvest season and degree of maturity in hive (Perez-Arquille et al 1993;Sanz et al 1995) and this parameter is highly significant considering the shelf-life of honey during storage. Moisture content between 16.0-18.0% indicates a proper degree of maturity.…”
Section: Resultsmentioning
confidence: 99%
“…If moisture content of honey is more than 19 %, it starts to ferment, to spoil, to lose flavor, to granulate irregularly and to separate into two layers during storage, thus, reduces its shelf life (Dustmann 1993). It has been reported in literature that if moisture content of honey is below 17 %, fermentation of honey will not occur irrespective of the yeast count (Wakhle 1997;Sanz et al Parm Pal Singh is formerly senior research engineer S. S. Dhaliwal is formerly associate professor 1995). Therefore, it becomes imperative to dehydrate honey below 17 % moisture content for safe storage and to fetch higher price in market.…”
Section: Introductionmentioning
confidence: 99%